Coordination games, multiple equilibria and the timing of radio commercials - Andrew Sweeting (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2005)
This paper presents a model of an imperfect information coordination game which has multiple equilibria if the incentive of players to choose the same action is strong enough. It shows how the existence of multiple equilibria in the model and in data from multiple independent repetitions of the game can identify the parameters. The model is estimated using new data on the timing of commercials by music radio stations in 147 local radio markets. Stations may have an incentive to choose the same times for commercials because many listeners try to avoid commercials by switching stations. There is evidence of multiple equilibria, with commercials clustered at different times indifferent markets, during drivetime hours. The estimated incentive to coordinate has a modest effect on Nash equilibrium timing strategies but commercials would overlap almost perfectly if each station internalized how its timing affects the audience of commercials on other stations. Most markets stay in the same equilibrium for the duration of my data and the incentive to coordinate is larger in smaller markets and in markets with more concentrated station ownership.
Keywords: 330